Reducing Long-Term Costs While Preserving a Robust Strategic Airlift Fleet Options for the Current Fleet and Next-Generation Aircraft - Mouton, Christopher A. (RAND Corporation, 2013)
The current strategic airlift fleet will be reaching the end of its service life in the next few decades, which has raised concerns about the cost and possible budget spike that would result from the need to recapitalize that fleet. This monograph presents the results of a cost-effectiveness analysis to determine the best way to recapitalize the USAF intertheater (strategic) airlift fleet.